Optimization of pulse signals transmission - Azarenkov, Volodymyr Ilyich; Smolianiuk, Kateryna Romanivna (CPN Publishing Group, 2023)
The problem of measuring the require ensuring reliable operation of the equipment minimum levels of input pulse signals, taking into account the level of interference and the permissible power of dissipation of the pulse device is proposed to be solved. A methodology has been developed to guarantee reliable transmission of information at the design stages.
Keywords: pulse; information; digital signal; optimization; thermal mode; reliability